AB0156 Thymic stromal lymphopoietin (TSLP) in primary sjÖgren's syndrome and related lymphoma: the possible contribution of a novel growth factor. (15th June 2017) - Gandolfo, S; Fabro, C; Bulfoni, M; Russi, S; Masolini, P; Quartuccio, L; Cesselli, D; Vita, S De
Abstract : Background: Primary Sjögren's syndrome (pSS) is an autoimmune lymphoproliferative systemic disease with a higher risk of non-Hodgkin B cell lymphoma (NHL) evolution. In SS, salivary gland (SG) epithelium plays a crucial role in initiating and perpetuating the autoimmune response. Thymic stromal lymphopoietin (TSLP) is both an epithelial and lymphopoietic cytokine involved in the maintenance of immune tolerance at interfaces between body and environment and in the regulation of lymphocytes homeostasis. Objectives: To study TSLP in serum and SG biopsies of pSS patients stratified by the lymphoproliferative histopathologic status, from fully benign lesions (fbSS) to myoepithelial sialoadenitis (MESA) and to NHL, in order to evaluate a possible role of TSLP in SS pathogenesis and in lymphoma evolution. Methods: Serum TSLP levels were determined by ELISA in pSS patients (n=30: 12 fbSS, 10 MESA, 8 NHL) and in controls (healthy blood donors - HD n=20; non-autoimmune sicca without SS - nSS n=10). TSLP was also studied by immunohistochemistry in SG biopsies of the same patients and nSS controls. Correlations with clinical and histopathologic parameters were performed. Of note, sequential samples were also included from three patients evolving from fbSS to NHL. Results: TSLP serum levels were significantly higher in pSS compared to nSS (p=0.03) and HD (p=0.0002), with a progressive significant increase from fbSS to MESA (p=0.004) and finally to NHL (NHL vs fbSS p<0.0001; NHL vs MESA p=0.003), where the increase was dramatic. This was observed also in metachronous samples from the three pSS patients evolving to NHL. A positive significant correlation between TSLP serum levels and disease activity assessed by ESSDAI was found (p<0.0001). Of note, in the affected tissue, TSLP showed an opposite pattern of expression than in the serum. Concerning the salivary epithelium, a declining expression of TSLP was shown from fbSS (expression was similar to nSS) to MESA and finally to NHL. Strikingly, however, the three pSS patients evolving to lymphoma were the only ones showing a low TSLP epithelial expression also at baseline. Concerning the glandular lymphoid infiltrate, the TSLP expression again decreased with progression to NHL. Again, the three pSS patients evolving to lymphoma were the only ones showing a low TSLP inflammatory expression also at baseline. Conclusions: Serum TSLP increases in pSS and correlates with lymphoma progression. Discrepancies are however observed between serum levels and tissue TSLP expression: while the baseline TSLP tissue expression is evident and similar to controls, tissue TSLP decreases with lymphoma progression. TSLP likely represents an additional growth factor and biomarker for pSS pathogenesis and lymphoproliferation. Disclosure of Interest: None declared